Xerotolerance: A New Property in Exiguobacterium Genus - María Castillo López; Beatriz Galán; Manuel Carmona; Juana María Navarro Llorens; Juli Peretó; Manuel Porcar; Luis Getino; Elías R. Olivera; José M. Luengo; Laura Castro; José Luís García (Microorganisms, 2021)
The highly xerotolerant bacterium classified as Exiguobacterium sp. Helios isolated from a solar panel in Spain showed a close relationship to Exiguobacterium sibiricum 255-15 isolated from Siberian permafrost. Xerotolerance has not been previously described as a characteristic of the extremely diverse Exiguobacterium genus, but both strains Helios and 255-15 showed higher xerotolerance than that described in the reference xerotolerant model strain Deinococcusradiodurans. Significant changes observed in the cell morphology after their desiccation suggests that the structure of cellular surface plays an important role in xerotolerance. Apart from its remarkable resistance to desiccation, Exiguobacterium sp. Helios strain shows several polyextremophilic characteristics that make it a promising chassis for biotechnological applications. Exiguobacterium sp. Helios cells produce nanoparticles of selenium in the presence of selenite linked to its resistance mechanism. Using the Lactobacillus plasmid pRCR12 that harbors a cherry marker, we have developed a transformation protocol for Exiguobacterium sp. Helios strain, being the first time that a bacterium of Exiguobacterium genus has been genetically modified. The comparison of Exiguobacterium sp. Helios and E. sibiricum 255-15 genomes revealed several interesting similarities and differences. Both strains contain a complete set of competence-related DNA transformation genes, suggesting that they might have natural competence, and an incomplete set of genes involved in sporulation; moreover, these strains not produce spores, suggesting that these genes might be involved in xerotolerance.